2021
DOI: 10.3390/su13041983
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Development Evaluation of Population–Land–Industry in Counties of Western China: A Case Study of Shaanxi Province

Abstract: The 14th Five-Year Plan of China proposes promoting urbanization construction, with counties as an important carrier. In order to evaluate the urbanization development level of counties in Western China, this study established an index system of population, land, and industry, constructed the coupling coordination model, selected Shaanxi Province as a representative case, and evaluated the comprehensive development level and its coordination degree of urbanization at the county level. The results show that: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The literature combined with the actual policies of Shaanxi Province to investigate the level of coordinated development and integration of urban and rural economy in the province. Based on the theoretical basis, combined with development economics and regional economics and other disciplines, it comprehensively described the characteristics of coordinated development in Shaanxi Province, and described the transformation process [13]. Through the analysis of the traditional dual development and integration development process of Shaanxi Province, the comprehensive indicator evaluation system of urban-rural integration is improved to achieve principal component analysis and cluster analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The literature combined with the actual policies of Shaanxi Province to investigate the level of coordinated development and integration of urban and rural economy in the province. Based on the theoretical basis, combined with development economics and regional economics and other disciplines, it comprehensively described the characteristics of coordinated development in Shaanxi Province, and described the transformation process [13]. Through the analysis of the traditional dual development and integration development process of Shaanxi Province, the comprehensive indicator evaluation system of urban-rural integration is improved to achieve principal component analysis and cluster analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Xu et al [39] constructed an index system for the comprehensive evaluation of three subsystems of urbanization (population, economy, and land urbanization) based on the theory of coordinated development, and they explored the spatial-temporal characteristics of overall coordination and paired coordination of population, land, and economic urbanization with an entropy method, coupling coordination degree model and spatial autocorrelation analysis. Niu et al [40] established an index system incorporating population, land, and industry, and they constructed a coupling and coordination model. Finally, they evaluated the comprehensive development level and the coordination degree of urbanization at the county level.…”
Section: Urbanizationmentioning
confidence: 99%
“…After consulting the relevant literature, it was found that there are fewer studies on the establishment of the urbanization level evaluation index system from the perspective of population, economy, land, and society [40,[48][49][50]. The urban resilience evaluation index system is mostly based on the four aspects of population, economy, land and society [51][52][53][54], and the influence of communities and organizations are seldom considered [55][56][57].…”
Section: The Coupling and Coordination Relationship Between Urban Res...mentioning
confidence: 99%
“…As a type of urbanization actively promoted by the national new urbanization strategy in recent years, nearby urbanization is opposed to the urbanization away from home and is different from in situ urbanization and rural urbanization. In the process of nearby urbanization, the spatial direction of urbanization of the rural population is mainly county towns, that is sub-districts and town areas in the prefecture and counties, whereas the county area is the front line of the transformation of registration and economic income distribution [18,19]. Therefore, nearby urbanization can also be considered as the urbanization of county area.…”
Section: Urbanization In China's County Area: the Neglected Peri-urba...mentioning
confidence: 99%